Effects of Nanosilica on Compressive Strength and Durability Properties of Concrete with Different Water to Binder Ratios - Forood Torabian Isfahani; Elena Redaelli; Federica Lollini; Weiwen Li; Luca Bertolini (Advances in Materials Science and Engineering)
The effects of the addition of different nanosilica dosages (0.5%, 1%, and 1.5% with respect to cement) on compressive strength and durability properties of concrete with water/binder ratios 0.65, 0.55, and 0.5 were investigated. Water sorptivity, apparent chloride diffusion coefficient, electrical resistivity, and carbonation coefficient of concrete were measured. The results showed that compressive strength significantly improved in case of water/binder = 0.65, while for water/binder = 0.5 no change was found. Increasing nanosilica content, the water sorptivity decreased only for water/binder = 0.55. The addition of 0.5% nanosilica decreased the apparent chloride diffusion coefficient for water/binder = 0.65 and 0.55; however, higher nanosilica dosages did not decrease it with respect to reference value. The resistivity was elevated by 0.5% nanosilica for all water/binder ratios and by 1.5% nanosilica only for water/binder = 0.5. The carbonation coefficient was not notably affected by increasing nanosilica dosages and even adverse effect was observed for water/binder = 0.65. Further information of microstructure was also provided through characterization techniques such as X-ray diffraction, thermal gravimetric analysis, mercury intrusion porosimetry, and scanning electron microscopy. The effectiveness of a certain nanosilica dosage addition into lower strength mixes was more noticeable, while, for the higher strength mix, the effectiveness was less.